Quantitative Analysis of Relationship Structure and Anionic Surfactant Micelle Concentration Critic With Semiempiris AM1 - Eva Vaulina Yulistia Delsy; Ponco Iswanto; Sandi Winaryo (Universitas Jenderal Soedirman, 2017)
This research determines the mathematical equation which calculate the Concentration Micelle Critic theoretical anionic surfactant. The research was conducted the depiction of each surfactant anionic three-dimensional compound models, followed by optimizing the model structure anionic surfactant by using AM1 calculation method. Furthermore the calculation of descriptors (QSPR method), then it was analyzed statistically using Multiple Linear Regression (MLR). The results of statistical calculations showed that to calculate the theoretical CMC anionic surfactant can use the QSPR equation: log CMC = 4.157+0.118qC1+7.698qC2+0.425Î±â0.010Âµ-0.129RDâ0.138 log P+0.021BMâ0.034Avdw, n = 100 ; r = 0.927 ; r2 = 0.860 ; SE = 0.352 ; F= 30.888 ; PRESS = 23.506